Does nesfatin-1 influence the hypothalamic–pituitary–gonadal axis in adult males with obstructive sleep apnoea? - Batura-Gabryel, Halina; Bromińska, Barbara; Sawicka-Gutaj, Nadia; Cyrańska-Chyrek, Ewa; Kuźnar-Kamińska, Barbara; Winiarska, Hanna; Kostrzewska, Magdalena; Zybek-Kocik, Ariadna; Hernik, Aleksandra; Wrotkowska, Elżbieta; Bielawska, Lena; Cofta, Szczepan; et al. (Scientific reports, 2019)
There is growing evidence that obstructive sleep apnoea (OSA) influences the hypothalamic–pituitary–gonadal axis (HPG axis) in men. The aim of the study was to assess the association of nesfatin-1 with HPG axis disturbances in OSA. This is a prospective study with consecutive enrolment. It comprises 72 newly diagnosed OSA patients ((AHI: apnoea-hypopnea index) 18 subjects: 5 ≤ AHI < 15; 24: 15 ≤ AHI < 30; 30: AHI ≥ 30) and a control group composed of 19 patients (AHI < 5). All patients underwent polysomnography and fasting blood collection for nesfatin-1, testosterone, luteinising hormone (LH), high-sensitivity C-reactive protein (hsCRP), aspartate transaminase (AST), alanine aminotransferase (ALT), creatinine and glucose. Groups had similar levels of LH, nesfatin-1 and testosterone (p = 0.87; p = 0.24; p = 0.08). Nesfatin-1 was not correlated to LH (p = 0.71), testosterone (p = 0.38), AHI (p = 0.34) or the oxygen desaturation index (ODI) (p = 0.69) either in the whole group, or in sub-groups. The study did not reveal any association between the HPG axis and nesfatin-1 in OSA adult males. It is possible that nesfatin-1 is not a mediator of HPG axis disturbances in adult patients with OSA.